The Long Noncoding RNA LINC00665 Facilitates c-Myc Transcriptional Activity via the miR-195-5p MYCBP Axis to Promote Progression of Lung Adenocarcinoma - Wang, Anpeng; Zhang, Te; Wei, Wei; Wang, Hui; Zhang, Zeyu; Yang, Wenming; Xia, Wenjie; Mao, Qixing; Xu, Lin; Jiang, Feng; Dong, Gaochao (Frontiers in Oncology, 2021)
Long noncoding RNAs (lncRNAs) have recently received growing substantial attention in cancer research due to their important roles in various cancer types. However, the underlying mechanisms and functions of lncRNAs, especially in lung adenocarcinoma (LUAD), remain elusive. Based on pan-cancer screening analyses, we identified that the noncoding RNA LINC00665 was up-regulated in lung adenocarcinoma, which was subsequently confirmed in clinical samples and cell lines. Higher expression of LINC00665 was positively associated with poor prognosis and advanced T stage. Next, using gain- and loss- of function approaches, we revealed that LINC00665 promotes cell proliferation, cell migration, invasion, and suppresses cell apoptosis in LUAD through in vitro and in vivo experiments. Additionally, our findings showed that LINC00665 was predominately localized in the cytoplasm so as to interact with Ago2 protein, which could function as miRNA sponges. The results of bioinformatics prediction and RNA pull-down assay indicated that LINC00665 directly interacted with miR-195-5p. This was also confirmed by fluorescence colocalization. Furthermore, luciferase reporter assay demonstrated that Myc binding protein (MYCBP, also called AMY-1), which enhanced c-Myc transcriptional activity, was the target gene of LINC00665 dependent on miR-195-5p. Finally, rescue functional assay results uncovered that the oncogenic capability of LINC00665 was dependent on miR-195-5p and c-Myc transcriptional activity. In summary, this work elucidates that LINC00665 accelerates LUAD progression via the miR-195-5p/MYCBP axis by acting as a competing endogenous RNA (ceRNA), suggesting that LINC00665 may represent a potential therapeutic target for clinical intervention of LUAD.